2015
DOI: 10.1177/1052562915594839
|View full text |Cite
|
Sign up to set email alerts
|

Management by Textbook

Abstract: Critical thinking is widely regarded as a crucial capability for competent management and also for any leadership role in society. In this article, we ask, “How do textbooks play a role in the weakness of many management graduates’ critical thinking skills?” Management teachers can find plentiful advice about best teaching practices, yet the critical skills gap remains. We argue that the nature and use of management textbooks intersect and interact with students’ epistemology to support a culture of surface le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 85 publications
0
12
0
1
Order By: Relevance
“…From a student-centered perspective and competencies-based work, it is essential for the textbooks to motivate students and stimulate their progress. Studies have shown that books play a crucial role in the development of critical thinking of students (Errington& Bubna-Litic, 2015). The notion "critical thinking" is used to describe thinking that is purposeful, reasoned and goal-directed.…”
Section: A Student As a Critical Thinkermentioning
confidence: 99%
“…From a student-centered perspective and competencies-based work, it is essential for the textbooks to motivate students and stimulate their progress. Studies have shown that books play a crucial role in the development of critical thinking of students (Errington& Bubna-Litic, 2015). The notion "critical thinking" is used to describe thinking that is purposeful, reasoned and goal-directed.…”
Section: A Student As a Critical Thinkermentioning
confidence: 99%
“…The research–practice gap in management is also reflected in the criticisms directed at management textbooks that are used in universities in introduction to management courses. The textbook is still a staple requirement of business schools largely due to the benefits it brings to teaching and in the vast majority of universities ME courses are textbook based (Errington & Bubna-Litic, 2015). Program directors declare certain texts as mandatory and this provides a control mechanism ensuring that several editions of the same class and year experience the same content.…”
Section: Criticizing Management Educationmentioning
confidence: 99%
“…In addition, the reading materials to be provided should be challenging texts. On this occasion, Errington, A., & Bubna-Litic, D. (2015) said the textbook could reinforce underdeveloped students" epistemology through limitations of content and position as passive recipients of an authoritative version of oversimplified knowledge". Thus, having appropriate materials, the students" academic and non-academic purposes can be improved.…”
Section: Introductionmentioning
confidence: 99%